2017
DOI: 10.1111/1758-2229.12530
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic‐di‐GMP signalling meets extracellular polysaccharide synthesis in Bacillus subtilis

Abstract: In order to resist harmful environmental conditions, many bacteria form multicellular aggregates called biofilms. In these biofilms, they protect themselves in a self-produced matrix consisting of extracellular polysaccharides, proteins and DNA. In many bacteria, biofilm formation is stimulated in the presence of the second messenger cyclic di-GMP. In this issue of Environmental Microbiology Reports, Bedrunka and Graumann have studied matrix production by the proteins encoded in the Bacillus subtilis ydaJKLMN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…C-di-GMP has been identified as an important signaling molecule that controls and regulates various cellular functions, such as virulence, motility (motile to sessile), biofilm formation and dispersion, flagellar motility, adhesion to surfaces, cell-cell signaling and cell differentiation [77]. C-di-GMP is involved in bacterial exopolysaccharide synthesis and biofilm formation in many bacterial species, such as B. subtilis and P. aeruginosa [78,79]. C-di-GMP performs its regulatory function by binding to a diverse group of effectors, such as kinases or phosphorylases [80], transcription factors [81], PilZ domain proteins [82], and riboswitches [83].…”
Section: Discussionmentioning
confidence: 99%
“…C-di-GMP has been identified as an important signaling molecule that controls and regulates various cellular functions, such as virulence, motility (motile to sessile), biofilm formation and dispersion, flagellar motility, adhesion to surfaces, cell-cell signaling and cell differentiation [77]. C-di-GMP is involved in bacterial exopolysaccharide synthesis and biofilm formation in many bacterial species, such as B. subtilis and P. aeruginosa [78,79]. C-di-GMP performs its regulatory function by binding to a diverse group of effectors, such as kinases or phosphorylases [80], transcription factors [81], PilZ domain proteins [82], and riboswitches [83].…”
Section: Discussionmentioning
confidence: 99%
“…The EPS produced by B. subtilis is mainly attributed to epsA-O operon and sacB-yveB-yveA transcriptional unit (Branda et al, 2006;Vlamakis et al, 2013;Arnaouteli et al, 2021). Recently, an additional unknown EPS encoded by ydaJKLMN operon was reported to contribute to extracellular matrix and thus biofilm formation in B. subtilis under laboratory conditions (Kampf and Stulke, 2017;Bedrunka and Graumann, 2017b). The analysis of the contributions of the different genes revealed that the YdaL, YdaM, and YdaN proteins provide the catalytic activities for EPS synthesis and YdaJ modifies the polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the contributions of the different genes revealed that the YdaL, YdaM, and YdaN proteins provide the catalytic activities for EPS synthesis and YdaJ modifies the polysaccharide. YdaK, which is also encoded within the putative EPS-synthesis operon ydaJ-N, is a cyclic di-GMP (c-di-GMP) binding signal transduction protein and is indispensable for EPS biosynthesis and complex colony biofilm formation in B. subtilis (Kampf and Stulke, 2017;Bedrunka and Graumann, 2017b). However, the function of the unknown EPS produced by YdaLMN is unclear.…”
Section: Introductionmentioning
confidence: 99%